The diagnostic significance of PGGT1B in psoriasis. Issue 2 (20th February 2021) - Hao, Zhimin; Lian, Ni; Gu, Heng; Chen, Min
Abstract: Psoriasis is a chronic and recurrent inflammatory skin disorder driven by a complex cascade of inflammatory mediators. The present study focused on the potential clinical significance of PGGT1B in psoriasis development. The peripheral blood mononuclear cells (PBMCs) were isolated from 81 psoriasis patients and 84 healthy controls, and the expression levels of PGGT1B in PBMCs were examined by quantitative real‐time polymerase chain reaction (RT‐qPCR) methods. Furthermore, we tested the relationship between the level of PGGT1B in PBMCs and psoriasis severity. Also, we analyzed the potential significance of PGGT1B in psoriasis diagnosis. Finally, patients with psoriasis were divided into progressive and stable stage groups, and the differential expression of PGGT1B, TNF‐α, IL‐17, and IFN‐γ between different phases were analyzed. PGGT1B was dramatically decreased in the psoriasis patients' PBMCs and negatively correlated with the Psoriasis Area and Severity Index (PASI). Moreover, receiver operating characteristics analysis showed the potential of differentially expressed PGGT1B in terms of distinguishing psoriasis patients from healthy controls. Finally, compared to the patients in the stable phase, PGGT1B was markedly reduced in patients' PBMCs in the progressive stage, while proinflammatory cytokines TNF‐α and IL‐17 were notably increased. PGGT1B was downregulated in psoriasis patients' PBMCs and may serve as a potential biomarker for the diagnosis and treatment of psoriasis.